2016
DOI: 10.1186/s12968-016-0317-3
|View full text |Cite
|
Sign up to set email alerts
|

Submillimeter diffusion tensor imaging and late gadolinium enhancement cardiovascular magnetic resonance of chronic myocardial infarction

Abstract: BackgroundKnowledge of the three-dimensional (3D) infarct structure and fiber orientation remodeling is essential for complete understanding of infarct pathophysiology and post-infarction electromechanical functioning of the heart. Accurate imaging of infarct microstructure necessitates imaging techniques that produce high image spatial resolution and high signal-to-noise ratio (SNR). The aim of this study is to provide detailed reconstruction of 3D chronic infarcts in order to characterize the infarct microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 43 publications
(50 reference statements)
1
31
2
1
Order By: Relevance
“…Fiber orientation in GZ, as estimated by the methodology described above, was the subject of concern, as there could be some level of fiber rearrangement not captured by those methodologies. The high-resolution imaging study by by Pashakhanloo et al 30 who used sub-millimeter-resolution DT and LGE-MRI on a clinical scanner to examine the detailed organization of the infarct structure in the ventricles. The study demonstrated that the epi-to-endo progression of the diffusion tensor primary eigenvector is preserved in infarcted parts of the wall in human (Figure 2) and in porcine hearts, justifying the adoption of a rule-based approach to fiber orientation estimation in the zone of infarct.…”
Section: How To Construct a Virtual Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…Fiber orientation in GZ, as estimated by the methodology described above, was the subject of concern, as there could be some level of fiber rearrangement not captured by those methodologies. The high-resolution imaging study by by Pashakhanloo et al 30 who used sub-millimeter-resolution DT and LGE-MRI on a clinical scanner to examine the detailed organization of the infarct structure in the ventricles. The study demonstrated that the epi-to-endo progression of the diffusion tensor primary eigenvector is preserved in infarcted parts of the wall in human (Figure 2) and in porcine hearts, justifying the adoption of a rule-based approach to fiber orientation estimation in the zone of infarct.…”
Section: How To Construct a Virtual Heartmentioning
confidence: 99%
“…C Transmural angle profiles measured in two segments from non-infarcted and infarcted regions ( a and b in panel A left ). Modified from Pashakhanloo et al 30 under the Creative Commons license.…”
Section: Figurementioning
confidence: 99%
“…In addition, abnormalities in HA may not be seen in all cases of myocardial injury,40 although calculating HA variance improves sensitivity for infarct detection 41. PA, in contrast, is highly uniform throughout the normal LV except for small areas at the apex and right ventricular insertion points.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the arrangement of cardiomyocytes in the atria and ventricles follows a specific configuration that has been studied both in animal and human hearts and has permitted the definition of mathematical models that describe it . To obtain the patient‐specific fibre orientation of the ventricular tissue, non‐trivial techniques such as diffusion tensor MRI have to be used . However, because of the long acquisition times required and the fact that the heart is beating only a few heart planes can be imaged in vivo, and the rest have to be interpolated, which hampers the original goal.…”
Section: Introductionmentioning
confidence: 99%
“…8 To obtain the patient-specific fibre orientation of the ventricular tissue, non-trivial techniques such as diffusion tensor MRI have to be used. 9 However, because of the long acquisition times required and the fact that the heart is beating only a few heart planes can be imaged in vivo, and the rest have to be interpolated, which hampers the original goal.…”
Section: Introductionmentioning
confidence: 99%